ENERGY ANALYSIS OF LIPID EXTRACTION OF Scenedesmus sp. PRODUCED IN PILOT SCALE - Schroeder, L.; Scherer, M. D.; Balmant, W.; Mariano, A. B.; Vargas, J. V. C. (Revista de Engenharia Térmica, 2015)
he production of biodiesel from lipids extracted from microalgae biomass is a promising approach to biofuels. However, this approach is still not commercialized because of the high costs of processes associated with, for example, time consumption and / or biomass drying with intense energy usage. However, it was not possible to show extraction methods among the lipids existing in the literature, which could be applied specifically to the extraction of lipids from the microalgae Scenedesmus sp. from the large-scale wet biomass, which is the current challenge faced by the Center for Research and Development of Sustainable Energy Auto (NPDEAS). Therefore, in this study, the possibility of avoiding the drying process, and extracting lipids directly from humid biomass, using the saponification method, was tested and compared with conventional Bligh and Dyer extraction (B & D). This study introduced the cultivation of microalgae Scenedesmus sp. compact tubular photobioreactors 12 m3 in area 10 m2 (8 x 5 x 2 m). The classical method of lipid extraction from microalgae - B & D - brings many pigments and polar lipids that exist in the biomass and the conversion rate was only 65-66%, whereas the recovery of fatty material in the wet biomass by the saponification method showed high conversion rate (90-95%). Therefore, the saponification process showed a high recovery of fatty acids that can be easily converted into biodiesel by esterification, and it was shown that the stage of drying the biomass can be removed without losing the fatty acids. In relation to the energy usage in the process, it was shown that drying the biomass for extraction of fatty acids uses more energy than that produced in the final product, biodiesel, showing that the removal of fatty acids of the wet biomass is of strategic importance to the viability of microalgae biodiesel.